FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEGAWAI FEB UIN SYARIF HIDAYATULLAH, JAKARTA DALAM MEMBAYAR ZAKAT PROFESI - Nurul Ichsan Hasan; Indra Nur Rahmat (Ekonomi Islam, 2023)
This study aims to analyze the factors that influence the decisions of employees at the Faculty of Economics and Business in carrying out professional zakat, including religiosity, altruism, motivation, knowledge and fintech. The data used in this study were primary data obtained from questionnaires and interviews. The method used is partial least squares (PLS). The population of this study were all employees of the Faculty of Economics at UIN Syarif Hidayatullah Jakarta, totaling 183 respondents, and the sample was 72 respondents. The results of this study indicate that the variables of religiosity, altruism, motivation, knowledge and fintech have a significant effect on employee tithe decisions. Adjusted R-square value of 0.894%. This means that the variables of religiosity, altruism, motivation, knowledge and fintech affect the decision to give professional zakat by 89%, while the remaining 11% is influenced by other variables outside the model examined. This research can be used as a reference in comparing the same research objects, especially regarding the analysis of factors that influence the decision to pay zakat, and as a reference to better understand people's behavior in their decision to pay zakat so that it can improve the performance of zakat institutions in collecting funds.